2007
DOI: 10.1038/sj.npp.1301312
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Glutamate Receptor Expression in the Medial Temporal Lobe in Schizophrenia and Mood Disorders

Abstract: Pharmacological and anatomical evidence suggests that abnormal glutamate neurotransmission may be associated with the pathophysiology of schizophrenia and mood disorders. Medial temporal lobe structural alterations have been implicated in schizophrenia and to a lesser extent in mood disorders. To comprehensively examine the ionotropic glutamate receptors in these illnesses, we used in situ hybridization to determine transcript expression of N-methyl-D-aspartate (NMDA), a-amino-3-hydroxy-5-methyl-4-isoxazole pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
216
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 376 publications
(237 citation statements)
references
References 117 publications
13
216
1
2
Order By: Relevance
“…and apoptosis or degeneration [54] . In fact, recent research has revealed that the levels of AMPARs and NMDARs decrease in both depressed patients and depressive animal models after long-term stress, and this decline may be attributed to the over-activation of GRs and degradation of glutamate receptors [55,56] . (Fig.…”
Section: The Infl Ammatory Cytokine Hypothesis Of Depression and Relamentioning
confidence: 99%
“…and apoptosis or degeneration [54] . In fact, recent research has revealed that the levels of AMPARs and NMDARs decrease in both depressed patients and depressive animal models after long-term stress, and this decline may be attributed to the over-activation of GRs and degradation of glutamate receptors [55,56] . (Fig.…”
Section: The Infl Ammatory Cytokine Hypothesis Of Depression and Relamentioning
confidence: 99%
“…[S 35 ]-labeled sense and antisense RNA probes were synthesized using SP6 and T7 RNA polymerase as previously described [45]. Briefly, 100 μCi dried [S 35 ]UTP was mixed with 1.5 μg linearized plasmid, 2 μl transcription buffer (5×; Promega), 3 mM NTPs (CTP, ATP, GTP), 1 μl 0.1 M dithiothreitol (DTT), 0.5 μl RNAse inhibitor and 25 units SP6 or T7 (Promega) in a total volume of 10 μl and incubated at 37°C for 2 h. Following incubation, probes were DNAse treated (1 μl DNAse1 for 15 min at room temperature (RT)), diluted in G50-50 buffer (100 mM Tris-HCl, 12.5 mM EDTA, 150 mM NaCl, and 0.2% sodium dodecyl sulfate, pH 7.5) and purified using micro Bio-Spin P-30 chromatography columns (Bio-Rad).…”
Section: Probe Labeling and In-situ Hybridizationmentioning
confidence: 99%
“…[124][125][126] This is of particular interest to the AA hypothesis as NMDA-mediated receptor stimulation increases the intracellular level of calcium, an activator of cPLA 2 . 127 Basselin and co-workers 40,128 found that acute administration of subconvulsant Collectively, these studies suggest that lithium alters AA signaling via PLA 2 as coupled to a variety of neuroreceptor subtypes (NMDA, serotonergic, dopaminergic and cholinergic) and are consistent with lithiumnormalizing neurotransmission imbalances that may account for the symptoms of bipolar disorder.…”
Section: Observations Related To Aa In Bipolar Disorder Patientsmentioning
confidence: 99%